Evaluation of segregating guava (Psidium guajava) progenies for their pomological and biochemical parameters - CHANDANA, M R; GOSWAMI, A K; SINGH, S K; KUMAR, CHAVLESH; RANA, V S; RUDRA, SHALINI GAUR; GOSWAMI, SUNEHA; SHARMA, R M; KUMAR, RAJEEV RANJAN (The Indian Journal of Agricultural Sciences, 2025)
The perennial guava (Psidium guajava L.) tree, characterized by a heterozygous genetic constitution, has been exploited for commercial cultivation of novel recombinants (through vegetative multiplication) obtained via traditional breeding. The current study was carried out during 2021–2022 at ICAR-Indian Agricultural Research Institute, New Delhi to evaluate19 guava genotypes, including parental lines and hybrids, for various physical and biochemical parameters in order to explore the potential of hybridization. The fruit morphological parameters, such as fruit weight, pulp weight, seed hardness, seed weight/fruit, and pulp-to-seed weight ratio, as well as biochemical parameters like titratable acidity, total phenolics, total flavonoids, total antioxidant capacity, and total carotenoids, exhibited coefficient variations greater than 20% in selected guava genotypes. The hybrid GH-2017-8B (W) had a maximum fruit diameter (6.88 cm), fruit weight (175.67 g) and pulp weight (172.08 g), while hybrid GH-2017-4F had significantly higher titratable acidity (0.62%) and ascorbic acid content (285.03 mg/100 g pulp). The hybrid GH-2017-2C had a minimum number of seeds/fruit (222.33), seed weight/fruit (2.41 g) and maximum pulp: seed weight ratio (64.66) and higher total phenolic content (194.97 mg/100 g Gallic Acid Equivalent Fresh weight). The hybrid GH-2017-6C was found superior for total flavonoids (92.53 mg/100 g FW). In contrast, hybrid GH-2017-1F had higher total soluble solids (12.54oBrix), total carotenoids (0.54 mg/100 g FW) and total sugars (9.09%) content. The fruit shape varied from roundish to ovate, the pulp colour from red to yellow and yellow-white, while the peel colour varied from yellow-green to pink. Hence, the hybrids GH-2017-4F, GH-2017-2C, GH-2017-6C, and GH-2017-1F were found to be superior to the selected guava genotypes.